2014
DOI: 10.1007/s12178-014-9208-0
|View full text |Cite
|
Sign up to set email alerts
|

Matching residency numbers to the workforce needs

Abstract: Matching the number of surgeons to the demands for orthopedic services has been notoriously difficult. Not only does one need to evaluate current trends in the supply and provision of services but anticipate the impact of future reforms on these variables. The British Orthopaedic Association has aspired to provide consultant to population ratio of 1:15,000 by 2020. Currently, the orthopedic community is tasked with providing care for an aging population with soaring levels of obesity; with both of these factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…10 -13 Although advanced data detailing physician need have allowed medical students, residents, and training programs to make informed decisions, a disconnect remains between the number of physicians being trained and the existing demand. 14 This is further complicated by the paucity of workforce data.…”
Section: Introductionmentioning
confidence: 99%
“…10 -13 Although advanced data detailing physician need have allowed medical students, residents, and training programs to make informed decisions, a disconnect remains between the number of physicians being trained and the existing demand. 14 This is further complicated by the paucity of workforce data.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been speculated that the demand for orthopedic surgeons who address these patients will only rise in the coming years due to rising obesity rates among specific demographics, particularly the elderly [ 3 ]. Total hip arthroplasty (THA) and total knee arthroplasty (TKA) have been identified as viable surgical therapeutic options for the therapy of osteoarthritis, involving the replacement of deteriorating joints with synthetic components that allow pain-free motion [ 4 ]. A prior study in Saudi Arabia found that, despite public concern and rejection of techniques like THA and TKA, there has been a surge in TKA cases in recent years, with excellent improvements in knee function and pain reduction [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study of 225 rural hospitals in the United States, just 30% had at least one full-time orthopedic surgeon. As a result, residents in such communities must drive an average of 55 miles for orthopedic emergencies, which may result in the patient's condition deteriorating before receiving medical care [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation